DETERMINASI KEMUDAHAN AKSES LAYANAN DAN SKEMA BAGI HASIL (PROFIT SHARING) TERHADAP LOYALITAS ANGGOTA BMT KUBE COLOMADU SEJAHTERA, KARANGANYAR - Della Sephia Hardani; Iin Emy Prastiwi; Abdul Haris Romdhoni (JMBEKO : Jurnal Manajemen, Bisnis & Eco-Industri, 2026)
This study aims to analyze the effect of product quality and store layout on customer satisfaction at UMKM RM Kebon Keong Cengklik Boyolali. This research employs a quantitative approach using multiple linear regression with an accidental sampling technique involving 97 respondents determined through the Lemeshow formula. Data were collected through questionnaires and analyzed to examine the effect of each variable. The results indicate that product quality and store layout have a partially positive and significant effect on customer satisfaction. The findings further show that product quality and store layout partially and significantly influence customer satisfaction, meaning that the better these two aspects are implemented, the higher the level of customer satisfaction at UMKM RM Kebon Keong Cengklik Boyolali.